If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 12 = 162 Reorder the terms: 12 + 5x = 162 Solving 12 + 5x = 162 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 5x = 162 + -12 Combine like terms: 12 + -12 = 0 0 + 5x = 162 + -12 5x = 162 + -12 Combine like terms: 162 + -12 = 150 5x = 150 Divide each side by '5'. x = 30 Simplifying x = 30
| 6n-1=-83 | | 3-2(1-8x)=4(6x+2)-7 | | 5x-2b=4 | | 7x+3b=23 | | x^2=342-x | | 5=5(x-2)-(x-7) | | 9x+9+11+11x=180 | | p-3(n-5)=30 | | 2-4-3x=3-4 | | 8e(-e)=10 | | x^2-2mx+m^2-m+1=0 | | -7+7x=-x-8(-2-x) | | 16x^2+64x-48=0 | | Log(9)(X)=1/2 | | ((24x^2)-2c-11)=0 | | Log(32)(X)=1/5 | | (24x^2c-11)=0 | | 5x/24=39 | | F=B(1+rt) | | 7s=5 | | 3x^2+xy-2y^2=o | | 3p^2-pq-2q^2=0 | | 4=3G | | 3x+35=8 | | 3(6x-5)+15x= | | F(x)=x^3-7x^2+24x-18 | | 2*x+0.5x+0.25x+1=100 | | F(x)=x^3+24x^2+7x-18 | | 584000= | | 3n^4-6n^2+9n=0 | | (1)4x+2=5 | | Y=-1x-(4) |